2006
DOI: 10.1007/s00508-006-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-Lymphknoten bei oralen und oropharyngealen epithelialen Tumoren

Abstract: Carcinomatous metastases in regional lymph nodes worsen substantially the prognosis of patients with oral cavity and oropharyngeal cancer. Due to the high probability of occult metastasis (about 30%), during surgical resection of the primary tumor usually also elective dissection of lymph nodes is performed. Opinions on the extent of the elective neck dissection still differ, whereas selective dissection increasingly gains in importance. The aim of selective dissections, based on the predictability of formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…Overall regional nodal and systemic recurrence of 5.0% in our study group during the 46 months follow-up period is quite similar to other recent published data (22,(24)(25)(26)(27)(28)(29). The false negative rate of 1.3% is less than 5% that is generally considered acceptable (28).…”
Section: Discussionsupporting
confidence: 90%
“…Overall regional nodal and systemic recurrence of 5.0% in our study group during the 46 months follow-up period is quite similar to other recent published data (22,(24)(25)(26)(27)(28)(29). The false negative rate of 1.3% is less than 5% that is generally considered acceptable (28).…”
Section: Discussionsupporting
confidence: 90%
“…For 8 of 120 remaining records, full‐text could not be retrieved, leaving 112 records for assessment of eligibility. All inclusion criteria were met in 19 articles and these were included in the analysis 30–48 . Reasons for exclusion and the flow of information through the review process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…All inclusion criteria were met in 19 articles and these were included in the analysis. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 Reasons for exclusion and the flow of information through the review process are shown in Figure 1 . The included studies reported the results of SLNB in a total of 377 patients with oropharyngeal ( n = 162), laryngeal ( n = 181), or hypopharyngeal ( n = 34) SCC.…”
Section: Resultsmentioning
confidence: 99%
“…Für das Oropharynxkarzinom werden in der Literatur Raten zwischen 20-38 % angegeben [19,22,[30][31][32][33][34]. Wird durch das klinische Staging eine cN0-Situation festgestellt, so kann in 11-30 % der Fälle dennoch ein histopathologischer Lymphknotenbefall nachgewiesen werden [18,35,36]. Die Ergebnisse unserer Studie mit einer hohen Rate an klinischen Unterschätzungen, Überschätzungen und einer hohen Rate an okkulten Metastasen, die durch die Literatur bestätigt werden, unterstreichen den Stellenwert der elektiven ND (chirurgisches Staging) als diagnostisches Verfahren.…”
Section: üBerlebenswahrscheinlichkeitunclassified
“…Die Ergebnisse unserer Studie mit einer hohen Rate an klinischen Unterschätzungen, Überschätzungen und einer hohen Rate an okkulten Metastasen, die durch die Literatur bestätigt werden, unterstreichen den Stellenwert der elektiven ND (chirurgisches Staging) als diagnostisches Verfahren. Patienten, die erst nach dem Auftreten klinischer Metastasen operiert werden, weisen eine geringere Überlebensrate auf als Patienten, die mit einer elektiven ND therapiert wurden [36,37]. Die Notwendigkeit einer elektiven Behandlung bei einer cN0-Situation ergibt sich auch aus der Tatsache, dass kein bildgebendes Verfahren befähigt ist, okkulte Metastasen und den N-Status zuverlässig zu bestimmen [22].…”
Section: üBerlebenswahrscheinlichkeitunclassified